1996
DOI: 10.1046/j.1365-2133.1996.d01-1095.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelin-1 in hyperpigmentation in seborrhoeic keratosis

Abstract: Seborrhoeic keratosis (SK) is a benign epidermal tumour with a varying degree of pigmentation. We have recently demonstrated that endothelin-1 (ET-1) is a strong keratinocyte-derived mitogen and melanogen for human melanocytes in UVB-induced melanosis. To clarify the role of ET-1 in hyperpigmentation in SK, we have used immunohistochemistry and reverse transcription-polymerase chain reaction (RT-PCR) to see whether the production of ET-1 is accentuated in SK. Immunohistochemical analysis in SK (n = 7; acanthot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 11 publications
5
41
0
1
Order By: Relevance
“…16 Therefore, our result further confirmed this observation in SK. The observation of increased expression ET-1, ET-2, and ETRB by BCC is reported here for the first time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…16 Therefore, our result further confirmed this observation in SK. The observation of increased expression ET-1, ET-2, and ETRB by BCC is reported here for the first time.…”
Section: Discussionsupporting
confidence: 93%
“…pigmentation. 16 However, since only about half of the SK and none of the BCCs analyzed in this investigation were pigmented, increased expression of ET pathway genes is not likely to be of major significance in regulating lesional pigmentation. The observation that ET pathway blockade resulted in marked decrease in keratinocyte survival in serum-free medium (see Figure 4) suggests another possible function of activated ET pathways in nonmelanoma skin cancers.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that expression of ET-1 23) and its receptors is increased 24) in seborrhoeic keratosis and in senile pigmented freckles. Involvement of a mechanism similar to the UVB-induced activation of melanocytes has been suggested for these pigmentation disorders, and thus treatment with the extract of A. officinalis might also be effective in whitening other than hyperpigmentary conditions associated with ET-1 function.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Furthermore, type IV Waardenburg syndrome (Shah-Waardenburg syndrome with Hirschsprung disease) is caused by mutations in the genes encoding ET-3 or ET B R. 48 In addition to their significance during the development of melanocytes, ET-1 and/or SCF are involved in melanocyte activation in several human pigmentary disorders such as lentigo senilis, dermatofibroma, café -aulait macules, and seborrehoic keratosis. [51][52][53][54][55] Especially in lentigo senilis, which is similar in histological aspects to UVB-melanosis, the enhanced expression of SCF and ET-1 occurs concomitantly with an increased expression of ET B R in the lesional pigmented epidermis.…”
mentioning
confidence: 97%